2017
DOI: 10.1016/j.neuroimage.2017.02.043
|View full text |Cite
|
Sign up to set email alerts
|

On the neural basis of sensory weighting: Alpha, beta and gamma modulations during complex movements

Abstract: . On the neural basis of sensory weighting: Alpha, beta and gamma modulations during complex movements. NeuroImage, Elsevier, 2017, 150, pp.200 -212. 10.1016/j.neuroimage.2017 Previous studies have revealed that visual and somatosensory information is processed as a function of its relevance during movement execution. We thus performed spectral decompositions of ongoing neural activities within the somatosensory and visual areas while human participants performed a complex visuomotor task. In this task, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 124 publications
(145 reference statements)
5
36
1
Order By: Relevance
“…The results of the effect of MVF on the alpha band functional connectivity between V1 and STG were consistent with the perspective that alpha oscillations (8-12 Hz) were considered to be a local marker of the somatosensory and visual cortices excitability level, with a smaller alpha power being associated with greater excitability (Pfurtscheller and Lopes da Silva, 1999;Anderson and Ding, 2011;Lebar et al, 2017). Lebar et al (2017), for example, found that alpha power significantly decreased in the visual cortex, indicating an increased gain of visual inputs during sensory incongruence compared with unperturbed conditions. Thus, this study further confirmed the role of alpha oscillation on visual sensory detectability and discriminability.…”
Section: Functional Connectivity Between Brain Regions Associated Witsupporting
confidence: 86%
“…The results of the effect of MVF on the alpha band functional connectivity between V1 and STG were consistent with the perspective that alpha oscillations (8-12 Hz) were considered to be a local marker of the somatosensory and visual cortices excitability level, with a smaller alpha power being associated with greater excitability (Pfurtscheller and Lopes da Silva, 1999;Anderson and Ding, 2011;Lebar et al, 2017). Lebar et al (2017), for example, found that alpha power significantly decreased in the visual cortex, indicating an increased gain of visual inputs during sensory incongruence compared with unperturbed conditions. Thus, this study further confirmed the role of alpha oscillation on visual sensory detectability and discriminability.…”
Section: Functional Connectivity Between Brain Regions Associated Witsupporting
confidence: 86%
“…It is established that movement accuracy is controlled by sensory feedback (Sperry, 1950 ; Wolpert et al, 1995 ) and experimental disturbances of sensory feedback reportedly reduce the accuracy of movements (Brandes et al, 2016 ; Lebar et al, 2017 ; Osumi et al, 2018 ). Additionally, subjective heaviness was altered with sensorimotor incongruence (Kuppuswamy et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies of healthy subjects indicate incongruence between the proprioception associated with motor commands and visual feedback altered limb perceptions, such as pain heaviness extra limb and limb loss (McCabe et al, 2005 ; Foell et al, 2013 ). We previously showed that sensorimotor incongruence causes peculiarity (Katayama et al, 2016 ), and others showed that experimental modulation of sensory feedback reduces the accuracy of movements (Brandes et al, 2016 ; Lebar et al, 2017 ). These reports have clarified the influence of spatial sensorimotor incongruence on body perceptions, peculiarity and motor control.…”
Section: Introductionmentioning
confidence: 98%
“…The functional state of the cerebral cortex can be partly indexed by spontaneous alpha oscillations, which would be dynamically modulated by hand movement and somatosensory feedback (43). For instance, alpha oscillations at bilateral central regions, originated from primary sensorimotor cortices, have been demonstrated to be desynchronized by voluntary movement and somatosensory stimulation, which is characterized as the decreased amplitude of the oscillations (44). Such a decrease was encoded by temporal anticipation, which subserved as a plausible mechanism for biasing subsequent perception and brain responses (45).…”
Section: The Analgesic Effect Associated With the Top-down Psychologimentioning
confidence: 99%